Проблеми формування та розвитку системи суб’єктів протидії корупції в Україні - Гречко, О. В.; Hrechko, O. V. (Вісник Кримінологічної Асоціації України. – 2023. – № 3 (30). – С. 177-185, 2023)
У статті наголошено на тому, що органи, які мають більшу інституціональну незалежність демонструють кращу ефективність у розслідуванні правопорушень та успішному притягненні до відповідальності винних осіб, аніж органи, що знаходяться під прямим владним контролем і управлінням. Виокремлено ключові відмінності між категорією «суб’єкти протидії корупції, що підпорядковані вищому політичному керівництву держави» та категорією «незалежні суб’єкти протидії корупції». Викладено авторський підхід до класифікації вітчизняних суб’єктів протидії корупції за рівнем їх ефективності та прозорості. Зокрема, даний критерій охоплює оцінку успішності виявлення, розслідування та припинення корупційних діянь. Констатовано, що українські незалежні антикорупційні органи, такі як НАБУ і САП, є лідерами за цим показником і демонструють кращу результативність, аніж інші правоохоронні відомства.

The article emphasizes that bodies with greater institutional independence demonstrate better effectiveness in investigating offenses and successfully bringing guilty persons to justice than bodies under direct governmental control and management. The key differences between the category "anti-corruption entities subject to the highest political leadership of the state" and the category "independent anti-corruption entities" are highlighted. The author's approach to the classification of domestic anti-corruption entities according to the level of their efficiency and transparency is outlined. In particular, this criterion covers the evaluation of the success of detection, investigation and termination of corruption acts. It was established that Ukrainian independent anti-corruption bodies, such as NABU and SAP, are leaders in this indicator and demonstrate better performance than other law enforcement agencies. Attention was focused on the need to implement complex reforms aimed at strengthening the legal system, increasing transparency in power structures, and creating conditions for active public participation. The active participation of civil society in combating corruption was noted. Public organizations, journalists and activists highlight corruption schemes and expose violations of the law, providing valuable information to law enforcement officers. A general analysis of the activities of the National Agency for the Prevention of Corruption (NABU), the Specialized Anti-Corruption Prosecutor's Office (SAP), the National Agency for the Prevention of Corruption (NAZK) and the High AntiCorruption Court as components of the anti-corruption system was carried out, the characteristic features of which include the distribution of spheres of responsibility, independence from the authorities and the presence of a special status, support of international partners, promotion of democracy in Ukraine, ensuring the right of citizens to fair conditions for business and equal opportunities of access to the spheres of education and science, health care, culture and leisure of citizens, a significant level of transparency and openness.

В статье подчеркивается, что органы, имеющие большую институциональную независимость демонстрируют лучшую эффективность в расследовании правонарушений и успешном привлечении к ответственности виновных лиц, чем находящиеся под прямым властным контролем и управлением органы. Выделены ключевые различия между категорией «субъекты противодействия коррупции, подчиненные высшему политическому руководству государства» и категорией «независимые субъекты противодействия коррупции». Изложено авторский подход к классификации отечественных субъектов противодействия коррупции по степени их эффективности и прозрачности.
The problems of formation and development of a system of subjects anti-corruption in Ukraine
Keywords: корупція; система суб’єктів протидії; антикорупційні органи; правоохоронна система; протидія корупції; corruption; system of countermeasures; anti-corruption bodies; law enforcement system; countermeasures against corruption; коррупция; система субъектов противодействия; антикоррупционные органы; правоохранительная система; противодействие коррупции